Determination of Polyphenols in Lycium barbarum Leaves by High-Performance Liquid Chromatography–Tandem Mass Spectrometry. (24th March 2017) - Zhu, Li; Peng, Zumao; Zhang, Xieguang; Yang, Jun; Lai, Xiaofang; Yang, Guowu
ABSTRACT: High-performance liquid chromatography coupled with high-resolution mass spectrometry was used for the determination of polyphenols in Lycium barbarum leaves. Twenty compounds extracted by methanol–water were tentatively identified that included chlorogenic acids, flavonoids, and phenolic acids. Neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, isochlorogenic acid B, isochlorogenic acid A, and isochlorogenic acid C were identified in Chinese cultivated L. barbarum leaves for the first time. Caffeic acid and isoquercitrin were also present. The concentrations of these compounds in L. barbarum leaves were determined. The results showed that all analytes had linear calibration relationships with limits of detection from 0.318 to 3.35 ng mL −1 . The polyphenols and flavonoids in L. barbarum leaves provided strong 2, 2-diphenyl-1-picrylhydrazyl radical-scavenging capacity (IC50 of 23.1 ± 0.4 to 26.0 ± 0.4 µg mL −1 ). This method is suitable for the determination of polyphenols in L. barbarum leaves, which provide polyphenols with suitable antioxidant activity.